Obstructive Sleep Apnea Syndrome (OSAS): evaluation and treatment of odontostomatological problems - Ierardo, Gaetano; Luzzi, Valeria; Polimeni, Antonella (La Medicina del Lavoro, 2017)
The Obstructive Sleep Apnea Syndrome (OSAS) is a breathing disorder characterized by repeated episodes of apnea/hypopnea occurring during sleep and caused by the obstruction of the upper airway. As OSAS can have a significant impact on quality of life, an early diagnosis and a multi-specialized recognition become important. Therapeutic proposals include the Mandibular Advancement Devices (MADs), intraoral devices that induce a mandibular advancement during the night to eliminate snoring and apnea. Italian guidelines on dental aspects of OSAS in adults and children focus primarily on anamnestic and clinical methods by which the dentist, in a role of epidemiological sentinel, can first identify a patient with OSAS and then participate in the therapeutic process using specific orthodontic intraoral devices.